PENINGKATAN PRESTASI BELAJAR MATEMATIKA MATERI PROGRAM LINIER MELALUI PENERAPAN METODE PROBLEM SOLVING BERBANTUAN MICROSOFT TEAMS DIMASA PANDEMI COVID-19 - DYAH SATYARINI RATNANINGRUM (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
The goal to be achieved in this study is to determine the extent to which learning achievement in mathematics has increased in linear program material by applying the problem solving method assisted by Microsoft Teams during the Covid-19 pandemic. The data source for this research was students of class XI IPS 2 at SMAN 1 Kebomas, Gresik Regency, East Java Province with a total of 35 students. Time This research was conducted from 26 July to 27 October 2020 in the odd semester of the 2020/2021 school year for 4 months. The data collected is quantitative and qualitative data. Quantitative data is data obtained from the results of formative tests in each cycle. While the qualitative data is in the form of observations in each learning cycle. The data obtained is then converted with success criteria to find out whether student learning outcomes can be known how to improve. The results of the research on the application of the Microsoft Teams-assisted problem solving method during the Covid-19 pandemic to improve mathematics learning achievement in linear program material in class XI IPS 2 SMAN 1 Kebomas in the pre-cycle found only 8 students or 22.86% of all students. In cycle I there were a number of students who succeeded in increasing their learning outcomes by increasing by 8 to 16 students or 45.71%. In cycle II students who succeeded in increasing their learning outcomes reached 27 students or 77.41%. Student achievement in the pre-cycle with a class average of 50.17 and in the first cycle the class average was 65.03 and in the second cycle the class average was 82.40. From the research data obtained, it shows that the mathematics learning achievement in linear program material with the application of the problem solving method assisted by zoom metting during the Covid-19 pandemic has been successful so that it is feasible to be implemented at SMAN 1 Kebomas Gresik. ABSTRAKTujuan yang ingin dicapai dalam penelitian ini adalah untuk mengetahui sejauh mana peningkatan prestasi belajar Matematika materi program linier dengan penerapan metode problem solving berbantuan Microsoft teams dimasa pandemi covid-19. Sumber data penelitian ini adalah siswa kelas XI IPS 2 SMAN 1 Kebomas Kabupaten Gresik Provinsi Jawa Timur dengan jumlah ssiswa 35 siswa. Waktu Penelitian ini dilaksanakan pada 26 Juli sampai dengan 27 Oktober 2020 di semester ganjil tahun pelajaran 2020/2021 selama 4 Bulan. Data yang dikumpulkan adalah data kuantitatif dan kualitatif. Data kuantitatif adalah data yang diperoleh dari hasil tes formatif pada setiap siklus. Sedangkan data kualitatif berupa hasil observasi pada tiap siklus pembelajaran. Data yang diperoleh kemudian konversikan dengan kriteria keberhasilan untuk mengetahui apakah hasil belajar siswa dapat diketahui bagaimana peningkatannya. Hasil penelitian penerapan metode problem solving berbantuan Microsoft teams dimasa pandemi covid-19 untuk meningkatkan prestasi belajar Matematika materi program linier pada siswa kelas XI IPS 2 SMAN 1 Kebomas pada pra siklus didapatkan hanya 8 siswa atau 22,86% dari seluruh siswa. Pada siklus I ada sejumlah siswa yang berhasil meningkatkan hasil belajar bertambah 8 menjadi siswa 16 atau 45,71%. Pada siklus II siswa yang berhasil meningkat hasil belajarnya mencapai 27 siswa atau 77,41%. Prestasi belajar siswa pada pra siklus dengan rata-rata kelas 50,17 dan pada siklus I rata-rata kelas 65,03 serta pada siklus II rata-rata kelas 82,40. Dari data penelitian yang didapatkan menunjukan bahwa prestasi belajar Matematika materi program linier dengan penerapan metode problem solving berbantuan zoom metting dimasa pandemi covid-19 ini telah berhasil hingga layak untuk diterapkan di SMAN 1 Kebomas Gresik.